Comprehensive molecular analysis of immortalization hallmarks in thyroid cancer reveals new prognostic markers. Issue 8 (18th August 2022) - Montero‐Conde, Cristina; Leandro‐García, Luis Javier; Martínez‐Montes, Ángel M.; Martínez, Paula; Moya, Francisco J.; Letón, Rocío; Gil, Eduardo; Martínez‐Puente, Natalia; Guadalix, Sonsoles; Currás‐Freixes, Maria; García‐Tobar, Laura; Zafon, Carles; et al.
Abstract : Background: Comprehensive molecular studies on tumours are needed to delineate immortalization process steps and identify sensitive prognostic biomarkers in thyroid cancer. Methods and Results: In this study, we extensively characterize telomere‐related alterations in a series of 106 thyroid tumours with heterogeneous clinical outcomes. Using a custom‐designed RNA‐seq panel, we identified five telomerase holoenzyme‐complex genes upregulated in clinically aggressive tumours compared to tumours from long‐term disease‐free patients, being TERT and TERC denoted as independent prognostic markers by multivariate regression model analysis. Characterization of alterations related to TERT re‐expression revealed that promoter mutations, methylation and/or copy gains exclusively co‐occurred in clinically aggressive tumours. Quantitative‐FISH (fluorescence in situ hybridization) analysis of telomere lengths showed a significant shortening in these carcinomas, which matched with a high proliferative rate measured by Ki‐67 immunohistochemistry. RNA‐seq data analysis indicated that short‐telomere tumours exhibit an increased transcriptional activity in the 5‐Mb‐subtelomeric regions, site of several telomerase‐complex genes. Gene upregulation enrichment was significant for specific chromosome‐ends such as the 5p, where TERT is located. Co‐FISH analysis of 5p‐end and TERT loci showed a more relaxed chromatin configuration in short telomere‐length tumours compared to normal telomere‐length tumours. Conclusions: Overall, our findings support that telomere shortening leads to a 5p subtelomeric region reorganization, facilitating the transcription and accumulation of alterations at TERT‐locus . Abstract : This article comprehensively characterizes molecular alterations associated with immortalization and telomere length of a thyroid tumor series comprising the different clinical behaviors of the disease. The study proposes a model for the immortalization process and unveils a new marker of disease prognosis based on the chromatin spatial organization of 5pter and TERT ‐locus.